Neuropsychiatric aspects of long COVID: A comprehensive review - Kubota, Takafumi; Kuroda, Naoto; Sone, Daichi (Psychiatry and clinical neurosciences, 2023)
Although some patients have persistent symptoms or develop new symptoms following coronavirus disease 2019 (COVID‐19) infection, neuropsychiatric aspects of long COVID are not well known. This review summarizes and provides an update on the neuropsychiatric dimensions of long COVID. Its neuropsychiatric manifestations commonly include fatigue, cognitive impairment, sleep disorders, depression, anxiety, and post‐traumatic stress disorder. There are no specific tests for long COVID, but some characteristic findings such as hypometabolism on positron emission tomography have been reported. The possible mechanisms of long COVID include inflammation, ischemic effects, direct viral invasion, and social and environmental changes. Some patient characteristics and the severity and complications of acute COVID‐19 infection may be associated with an increased risk of neuropsychiatric symptoms. Long COVID may resolve spontaneously or persist, depending on the type of neuropsychiatric symptoms. Although established treatments are lacking, various psychological and pharmacological treatments have been attempted. Vaccination against COVID‐19 infection plays a key role in the prevention of long coronavirus disease. With differences among the SARS‐CoV‐2 variants, including the omicron variant, the aspects of long COVID are likely to change in the future. Further studies clarifying the aspects of long COVID to develop effective treatments are warranted. Overview of neuropsychiatric aspects of long COVID.